(untitled) (Phenomenology, Humanities and Sciences, 2020)
This article aims to deepen the discussion about the contemporary phenomenon called “time management”, from the Heideggerian ideas that surround the expression coined by him of “Era of the Technique”. It stands out; in particular, the philosopher’s reflections on calculating thought (operational, pragmatic and detached from the reflection of what is more proper and originating from the experience of being-in-the-world), the sense of occupation and the affective dispositions anguish and boredom.It seeks to understand the relationship between the current way of life - characteristically accelerated and superficial, the reification of a proclaimed need and pretense ability to “manage time” and the forgetting the experience of temporality as existential flow. It is intended, at the same time, to reflect critically on the changes, implications and impacts arising from the new social configurations produced by this way of thinking, whose foundations appear to be based on the modern conception of time as measure and product.